I would say, it is round, and flat on two sides, like a can, pipe, straw, unsharpened pencil, or a piece of your leg.
(0-0)÷(-3-5)=0
it is zero
Combine like terms
-6x^2+2y + -1 +2x^2 + -5y +3
( -6x^2+2x^2)+(2y-5y)+(-1+3)
= -4x^2+3y+2
Answer : C
I hope that's help !
Answer: x=
1
Step-by-step explanation: solve for x by simplifying both sides of the equation, then isolating the variable.
Answer:
a = 1
b = -1
Step-by-step explanation:
First, let's make equations out of those given f(x)'s
-4 = -3a + b
2 = 3a + b
We can use elimination method to get rid of the a real quick
-4 = b
2 = b
Add those together
-2 = 2b
Divide both sides by 2
-2/2 = 2b/2
b = -1
Plug in the new b in one of the original equations; I'm gonna use the bottom one
2 = 3a - 1
+ 1 + 1
3 = 3a
3/3 = 3a/3
a = 1